A Study of Implicature in Daredevil Web Series Movie - Fauzia, Fauzia; Prakoso, Isnaini Jalu Rakhmat (English Language Teaching Educational Journal, 2018)
This study is aimed to identify the implicature and their maxim violation and find out how the violating maxims occur in the movie. The study is conducted by using the qualitative method. The research object of this study is about implicature and the violation of the maxim. The subject of this study is a web series movie script entitled Daredevil, the scripts are taken from season 1 episode 1 until 3. To collect the data, the writer uses note taking technique. The writer uses pragmatic referential method (metode padan pragmatis) to analyze the data. The result shows 25 implicatures in Daredevil web series movie that occur because of its violation of the maxim.  There are 20% implicature by violating the maxim of quantity, 36% implicature by violating the maxim of quality, 26% implicature by violating the maxim of relation, 18% implicature by violating the maxim of manner. By violating the maxim, the characters produce some implied meanings which can be used to misleading the hearer. The implied meaning of the utterances refers to an expression of agreement, denial, refusal, acceptance and indirect sentence, it depends on how the character uses the implicature. Key words: Pragmatics, Context, Cooperative Principle, Implicature, Violating Maxim